Profiling Students’ Interpersonal Intelligence at SMPIT Buahati Islamic School Jakarta and Its Implications for Counseling Services - Magfirah, Nazla; Solihatun; Wulandari, Wenny (Eduscape : Journal of Education Insight, 2025)
Interpersonal intelligence is a crucial socio-emotional capacity that enables adolescents to build positive peer relationships, collaborate effectively, and regulate emotions in diverse school environments. This study aimed to describe the overall profile of students’ interpersonal intelligence at SMPIT Buahati Islamic School Jakarta and to identify its implications for guidance and counseling (BK) services. Using a quantitative survey design, data were collected from 60 Grade VIII students through a validated 23-item Likert-scale instrument (Cronbach’s α = 0.860) covering four domains: empathy, cooperation, interpersonal communication, and social skills. The findings revealed that most students demonstrated good interpersonal competence, particularly in cooperation, while interpersonal communication emerged as the weakest domain. This suggests that although students work well in teams, many struggle to articulate ideas clearly and confidently. These results highlight the importance of school-based counseling interventions that focus on improving communication, empathy, and social interaction skills. Strengthening these dimensions can support students’ emotional maturity, peer harmony, and readiness to engage in collaborative learning environments.